Recent Publications (Quarterly Journal of Economics, 1971)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 85, Issue 2, May 1971, Pages 363–364, https://doi.org/10.1093/qje/85.2.363 Published: 01 May 1971